(untitled) (Journal of Economic Research & Business Administration, 2025)
This study examined the nexus between retirement benefits and the standard of living of Osun State civil service retirees. The study identified pension schemes, gratuity, and healthcare services as the basic retirement benefits offered by the Osun State Government to retired civil servants as variables used to measure the standard of living of retired civil servants. A questionnaire as the research instrument was administered to 363 respondents obtained from the Nigeria Union of Pensioners in Osogbo, Osun State. Findings from the study showed that the pension scheme is adequate and there exists a strong relationship between the variables of retirement benefits (pension schemes, gratuity, and healthcare services), and the standard of living of the retirees. The study concluded that the module operandi of retirement benefits as currently being practiced affects the standard of living of retirees negatively and thus, recommended that the implementation of pension schemes, gratuity, and healthcare services should reflect socio-economic factors with priority on inflation and social support systems. Key words: pension schemes, gratuity, and healthcare benefits, standard of living, retirement, well-being.